What Makes Collaboration Work, And Die? Dissecting Leadership, Coherence, And Conflict Mechanisms - Sutrisno, Andang Nugrahena; Damanik, Janianton; Widaningrum, Ambar (Magister Ilmu Administrasi Publik, 2026)
This study investigates the institutional and relational foundations of stakeholder collaboration in Indonesia’s community-based tourism (CBT) governance. It addresses the gap in understanding why similar policy frameworks produce divergent governance outcomes across local contexts by employing a qualitative, causal-comparative case study of four tourism villages in Purworejo Regency. Kaligono, Ketawang, Patutrejo, and Cacaban Kidul constitute the four comparative cases. The analysis examines how differences in institutional design and actor asymmetries shape the formation and durability of collaborative arrangements. The study elucidates the mechanisms that generate effective collaboration, contribute to stagnation, or result in its complete absence. The findings clarify the conditions under which collaboration works, collapses, or never materializes across the four CBT villages. Collaboration is effective when leadership holds strong local legitimacy, institutional roles are clearly defined, and conflict-resolution mechanisms are trusted. Kaligono illustrates effective collaboration through facilitative leadership and coherent institutional alignment. Ketawang demonstrates episodic, event-driven collaboration that ultimately dies due to weak structural anchoring. Patutrejo illustrates how overlapping mandates and ineffective leadership lead to collaboration deteriorating into institutional rivalry. Cacaban Kidul represents a collaboration that never comes to life, a dormant governance arena where formal designations exist without activation. Three mechanisms, leadership brokerage, institutional coherence, and conflict accommodation, explain these divergent trajectories.